A novel DTC scheme for a sensorless five-phase IM drive under open-phase fault. Issue 2 (4th March 2019) - Echeikh, Hamdi; Kesraoui, Hichem; Trabelsi, Ramzi; Iqbal, Atif; Mimouni, Mohamed Faouzi
Abstract : Purpose: This paper aims to deal with direct torque controller when the five-phase induction motor drive in faulty operation. Precisely, open-phase fault condition is contemplated. Also, the DTC is combined with a speed-adaptive variable-structure observer based on sliding mode observer. Design methodology/approach: Two novel features are presented. First, the concept of the virtual voltage vector is presented, which eliminates low-frequency harmonic currents and simplifies analysis. Second, speed information is introduced into the selection of the inverter states. Findings: Direct torque control (DTC) is largely used in traditional three-phase drives as a backup to rotor-stator flux-oriented methods. The classic DTC strategy was primarily designed on the base of hysteresis controllers to control two independent variables (speed, torque and flux). Due to the additional degrees of freedom offered by multiphase machine, extensive works have been extended on the ensemble five-phase drives in healthy operation. In addition, the ability to continue the operation in faulty conditions is considering one of the main advantages of multiphase machines. One can find in the literature different approaches treating this subject. The applicability of DTC after the appearing of a fault has not been enclosed in the literature. Originality/value: Theoretical development is presented in details followed by simulation results using Matlab/Simulink to analyze the performance of the drive, comparing with the behavior during healthy situation.